Tupperware packaging / Anis Ayu Fatihah Ahmad Kamil - Ahmad Kamil, Anis Ayu Fatihah (2022)
Tupperware is well-known as the kitchen and household products, also it is particularly known for its line of plastics containers for food storage and preparation. In 2008, due to its success in developing the brand's name in China, India, and Indonesia, Tupperware received awards for "Most Favored Brand by Women" and "Company with the Best Corporate Face".